Role of Exercise Therapy in Prevention of Decline in Aging Muscle Function: Glucocorticoid Myopathy and Unloading - Teet Seene; Priit Kaasik (Journal of Aging Research)
Changes in skeletal muscle quantity and quality lead to disability in the aging population. Physiological changes in aging skeletal muscle are associated with a decline in mass, strength, and inability to maintain balance. Glucocorticoids, which are in wide exploitation in various clinical scenarios, lead to the loss of the myofibrillar apparatus, changes in the extracellular matrix, and a decrease in muscle strength and motor activity, particularly in the elderly. Exercise therapy has shown to be a useful tool for the prevention of different diseases, including glucocorticoid myopathy and muscle unloading in the elderly. The purpose of the paper is to discuss the possibilities of using exercise therapy in the prevention of glucocorticoid caused myopathy and unloading in the elderly and to describe relationships between the muscle contractile apparatus and the extracellular matrix in different types of aging muscles.